Diagnosing of Small Vessel Vasculitis Might be a Challenge – A Rare Case Report - Shahin, Md Abu; Khan, Mohammad Mamun; Shrestha, Swikriti; Abdal, Syed Jamil; Islam, Md Ariful; Choudhury, Minhaj Rahim (Bangladesh Medical Journal, 2020)
The term vasculitis refers to the inflammation of vessel walls. It may range in severity from a self-limited disorder in one single organ to a life-threatening disease due to multiple organ failure. Most patients with small vessel vasculitis present with constitutional symptoms like fever, malaise, weakness, fatigue and weight loss. To diagnose small vessel vasculitis, serology like ANCA, serum cryoglobulin and biopsy play an important role. Despite the serology and biopsy, diagnosing small vessel vasculitis occasionally remains challenging in resource constraint countries. Here we are reporting a case of a 26-year- old female who presented with purpura and neuropathy. The patient lacks clinical features like constitutional symptoms, renal involvement, upper airway involvement and her ANCA was negative. Depending on biopsy finding and skin and neurologic involvement, we diagnosed her as a case of small vessel vasculitis (unclassified). The patient improved with IV methylprednisolone followed by oral glucocorticoid treatment along with methotrexate. Although small vessel vasculitis has some typical features, diagnosis may often remain challenging even after biopsy. Bangladesh Med J. 2020 May; 49(2) : 41-43